THE SATISFACTION OF INDIRECT PUBLIC INTEREST IN THE INDUSTRIAL AND COMMERCIAL ACTIVITIES OF THE STATE: THE INDUSTRIAL AND COMMERCIAL ACTIVITY OF THE STATE AS A MEANS OF ECONOMIC INTERVENTION - CABRERA PANTOJA, JAIRO EDMUNDO (Constituição, Economia e Desenvolvimento: Revista Eletrônica da Academia Brasileira de Direito Constitucional, 2021)
The State has become what is currently known as a Social Rule of Law that is based on the protection and fulfillment of the public interest. However, when analyzing the role of the State, we observe that it does not always act under the postulates of empire or power, since, in specific cases, it is limited to regulations specific to the law that governs the individuals. Then, we find a legal phenomenon called voluntary submission of the administration to the private law, where the latter acts in uniform conditions for the individuals in the fulfillment of the purpose for which it was created. Thus, a new form of administrative activity is created through the industrial and commercial role of the State that finds its aim framed in the satisfaction of an indirect public interest, since the State, through these institutions, does not generate the direct collective satisfaction of its partners, but it seeks the collection of resources that can be transferred so that the State complies with its purposes.